If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32(x + -1) = -8(4x + -1x) + 24x Reorder the terms: 32(-1 + x) = -8(4x + -1x) + 24x (-1 * 32 + x * 32) = -8(4x + -1x) + 24x (-32 + 32x) = -8(4x + -1x) + 24x Combine like terms: 4x + -1x = 3x -32 + 32x = -8(3x) + 24x Remove parenthesis around (3x) -32 + 32x = -8 * 3x + 24x Multiply -8 * 3 -32 + 32x = -24x + 24x Combine like terms: -24x + 24x = 0 -32 + 32x = 0 Solving -32 + 32x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 32x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + 32x = 0 + 32 32x = 0 + 32 Combine like terms: 0 + 32 = 32 32x = 32 Divide each side by '32'. x = 1 Simplifying x = 1
| 7(x-7)=7x+14 | | (9x+2)=3x-23 | | 12m-12m=2(-12+12m)-12(10-10m) | | 3r-3=6 | | (x-4)(x^2+6x-1)= | | 20y+18x=10-18x | | 0.02(2t-7)=0.04(t+5)-0.34 | | 6.8x+2=5.8x | | m/2-1=11 | | 21=49-4(5-1w) | | 4t^2-52t+160=0 | | 2w+2(2w+6)=28 | | -9+7z+2-5z= | | k=7+9 | | 27=-9(y-5) | | 3m+(m+7n)-(2m+5n)= | | e^5k=32 | | -6u+-u= | | 5(x+1)-3(x-2)=17 | | .2k-(k+.34)=.67(k+3) | | -3(4y+1)-19=-8(y+4)+4y | | 8s+18=6(2s+3)-45 | | 2(2n+2)=7(4n+4)+4 | | X+0.3x=130 | | -(2y-3x)-x-(x+2y)= | | 3x+3y=2x+9 | | 5/6y=5-11/12y | | 2e^4x+1=4 | | (4a-b)-(a-2b)+b= | | 7a-3a-2a-a=16 | | 7(y+3)=28 | | 3(x+7)+4=7x-4(x-4) |